The XCAT science portal - Krishnan, Sriram; Bramley, Randall; Gannon, Dennis; Govindaraju, Madhusudhan; Indurkar, Rahul; Slominski, Aleksander; Temko, Benjamin; Alameda, Jay; Alkire, Richard; Drews, Timothy; Webb, Eric (Proceedings of the 2001 ACM/IEEE Conference on Supercomputing, 2001)
The design and prototype implementation of the XCAT Grid Science Portal is described in this paper. The portal lets grid application programmers easily script complex distributed computations and package these applications with simple interfaces for others to use. Each application is packaged as a "notebook" which consists of web pages and editable parameterized scripts. The portal is a workstation-based specialized "personal" web server, capable of executing the application scripts and launching remote grid applications for the user. The portal server can receive event streams published by the application and grid resource information published by Network Weather Service (NWS) [32] or Autopilot [15] sensors. Notebooks can be "published" and stored in web based archives for others to retrieve and modify. The XCAT Grid Science Portal has been tested with various applications, including the distributed simulation of chemical processes in semiconductor manufacturing and collaboratory support for X-ray crystallographers.